2009
DOI: 10.1073/pnas.0901123106
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical differentiation of stop consonants relates to reading and speech-in-noise perception

Abstract: Children with reading impairments have deficits in phonological awareness, phonemic categorization, speech-in-noise perception, and psychophysical tasks such as frequency and temporal discrimination. Many of these children also exhibit abnormal encoding of speech stimuli in the auditory brainstem, even though responses to click stimuli are normal. In typically developing children the auditory brainstem response reflects acoustic differences between contrastive stop consonants. The current study investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
262
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(284 citation statements)
references
References 70 publications
16
262
4
2
Order By: Relevance
“…These results demonstrate that assistive listening devices improve the neurophysiological representation of speech, specifically the rapid spectrotemporal components that are most vulnerable to noise. This latter finding is particularly interesting because it is formant transitions within speech syllables that have been shown in both behavioral and physiological studies to be most impaired in children with language and reading disorders (3,7). These data support a growing body of research suggesting that there may be a developmental continuum beginning in infancy that links individual differences in rapid auditory processing to individual differences in language development and subsequently to reading and other literacy skills.…”
Section: Auditory Intervention Improves Readingsupporting
confidence: 69%
“…These results demonstrate that assistive listening devices improve the neurophysiological representation of speech, specifically the rapid spectrotemporal components that are most vulnerable to noise. This latter finding is particularly interesting because it is formant transitions within speech syllables that have been shown in both behavioral and physiological studies to be most impaired in children with language and reading disorders (3,7). These data support a growing body of research suggesting that there may be a developmental continuum beginning in infancy that links individual differences in rapid auditory processing to individual differences in language development and subsequently to reading and other literacy skills.…”
Section: Auditory Intervention Improves Readingsupporting
confidence: 69%
“…These influences converge to make auditory midbrain a hub of cognitive, motor, and sensory processing. We speculate that top-down attentional and cognitive modulations caused an activity-driven enhancement in midbrain function, which progressively (i.e., with more training) drove the changes we observed (Polley et al, 2006;Hornickel et al, 2009;Bajo et al, 2010;Kraus and Chandrasekaran, 2010;Bajo and King, 2012). Uniquely, making music engages these systems in a positive, reinforcing, and active manner that offers neuroplastic potential beyond everyday listening experiences.…”
Section: Discussionmentioning
confidence: 88%
“…This suggests that music training transferred to non-music listening settings to influence automatic auditory processing. Importantly, these improvements were in processes that are important for everyday communication: previous investigations have revealed that, as groups, children who are better readers and children who hear better in noise show stronger neural distinctions of these same syllables (Hornickel et al, 2009;White-Schwoch and Kraus, 2013). These findings therefore provide support for the efficacy of community and co-curricular music programs to engender improvements in nervous system function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations